New and little known species of Kamimuria (Plecoptera: Perlidae) from Fujian of China - Li, Weihai; Kong, Fanbin; Liu, Siqi (Zootaxa, 2020)
Kamimuria shiae sp. n. and K. tenuilobata sp. n., two new perlid stoneflies from Wuyi Mountains of Fujian Province, eastern China, are described as new to science. The new species are compared with similar congeners. Kamimuria robusta Wu, 1948 is rediscovered from the type locality of the same mountain.